An MIP model to optimize a Colombian cash supply chain (2012)
Financial institutions operate a supply chain where only one product is moved across the network. Although the cash is kept in several nodes to service the demand of final customers, availability causes opportunity cost related with its investment options. When planning the inventory of cash that should be maintained across the network, transportation decisions are also expected to be made. Cash transportation has a high cost, associated with the high risk of theft. Increasing the inventory can reduce the need for transportation, but the opportunity cost can be very high. Moreover, the inventory is also related with the service level perceived for final customers; therefore because of low inventory some people are not able to make some transactions. The aim of this work is to find optimal decisions related with cash inventory and transportation across the network, trying to balance the cost of the service and the quality perceived for final users.